Correlation of Maternal Age with Prevalence of Chromosomal Anomalies in Patients of Anorectal Malformation - Dewanshi Mishra; Rakesh Kumar Verma; Archana Rani; Garima Sehgal; Anushree Pandey (Academia Anatomica International, 2019)
Introduction: Aims: To identify the Anorectal malformations patients in North Indian region and then study the karyotype of these patients to evaluate cytogenetic aberrations and then correlate it with the maternal age. Subjects and Methods: Forty eight patients of anorectal malformation were selected from Department of Paediatric Surgery, KGMU, UP, Lucknow. Blood samples were collected and their cytogenetic study was done in the Department of Anatomy, KGMU-U.P, Lucknow. Karyotypes obtained were further analysed. Results: Out of 48 children enrolled in the study, karyogram could be obtained for 45 cases (93.75%). Maternal age at the time of birth of the child was <30 years in 91.1% cases. There were only 8.9% women who were >30 years of age at the time of birth of the child. However, proportion of those with anomalies was significantly higher in >30 years age group (75%) as compared to that in <30 years age group (2.4%). Conclusion: Although low maternal age was found most commonly, but number of cases with chromosomal anomalies was reported more in >30 years of age, which could be due to increased risk of congenital anomalies and malformations with advanced age.